L’étude des emprunts lexicaux dans le roman de Faîza Guėne « Un homme ça ne pleure pas » - Fatima Zohra Belkacem Zerhouni; Wissam Chafi (Multilinguales)
Romanesque writing is a work of fictional art that has meaning. It is committed to and denounces certain community events linked to the exile and mutation of individuals throughout the world. Faïza Guène, who has a connection with the Maghreb, brings an almost similar conception on the obstacles she encounters in the short of her journey. While accepting displacement and progression, she presents herself as a local writer and an evolving cultural carrier.